EFFECT OF SPRAYING NANO-AMINO ACIDS AND IRON ON SOME YIELD CHARACTERISTICS AND THE CHEMICAL AND MEDICINAL CONTENT OF TWO CULTIVARES OF FENUGREEK PLANT, TRIGONELLA FOENUM-GRAECUM L - Amel Hussein khudhiar AL- Ibraheemi1 , Saadon Abdul-Hadi Saadon AL-Ajeel2 (Chelonian Research Foundation, 2024)
The experiment was carried out in the nursery of the Agricultural Division of the University of Kufa in Najaf Governorate for the season 2022-2023 to study the effect of spraying nano-amino acids and iron on some yield characteristics and the chemical and medicinal content of two varieties of the fenugreek plant, Trigonella foenum-graecum L., the local variety and the Indian variety. The experiment included eight treatments. It is an interaction between two varieties of fenugreek plant (local A1 and Indian A2) with four spray treatments: T1 control (distilled water), T2 (200 mg. L-1) nano-iron, T3 (2 ml. L-1) nano-amino acids, and T4. (200 mg.L -1+ 2 mL.L-1) nano-iron and nano-amino acids. A factorial experiment was carried out using a completely randomized design (C.R.D) with two factors: varieties and spray treatments, with three replicates. The means were compared according to Duncan's multinomial test at the probability level of 0.05. Measurements were taken at the end of the growing season. The results showed that foliar spraying of nano-amino acids and iron led to improvement in yield indicators and the chemical and medicinal content of all studied traits compared to control plants. The results of the study also showed that the T3 treatment (nano amino acids) gave the highest rates in most of the traits under study (pod length, number of pods, number of seeds, Choline, Peroxidase and Catalase when interacting with the local variety A1, as it reached 11.03 cm, 54.63 (pod. Plant-1), 14.00 (seed. pod-1), 0.44, 1.55, 1.42 (mg. ml-1), respectively. As for the Indian variety A2, it gave the highest rate of the alkaloid Trigonelline when interacting with treatment T3, amounting to 0.79( mg. ml-1). Keywords: Fenugreek, nano-iron, nano-amino acids, Trigonelline, Choline.